(untitled) (Al-Academy, 2024)
Digital TV platforms are the most important new media tools that seek to present themselves as alternative platforms for traditional TV channels. Different platforms to produce distinctive and unique content that pushes individuals to subscribe, and some platforms began looking for obtaining exclusive broadcasts for foreign and Arab shows. From here, the research tagged (the intellectual dimensions in the production of digital platforms films (Netflix platform as a model) was launched. The research included the research problem, the need for it, the importance of the research and its objectives.As for the second chapter, it included two topics, the first topic: the historical view of digital platforms, but in the second topic, it was entitled: The intellectual role of film production platforms. The third chapter included: the research methodology, the research community, the research tool, and then the sample analysis. As for the fourth chapter: results and conclusions, in which the results of the research were reviewed, including (the movie Black and Blue is a clear translation of the production policy on the Netflix platform, as it searches for intellectual, political and sometimes popular contents in order not to lose a specific category of viewers of the platform), then conclusions, proposals and recommendations The research concluded with a list of sources and references.